BKMT Kota Jayapura Dalam Mengembangkan Majelis Ta’lim Tingkat Mesjid - Zulihi, Zulihi; Yusuf, Muhamad (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
BKMT Jayapura in carrying out its duties in fact there is still a majelis ta'lim has not been tracked by BKMT, even in the implementation of religious activities BKMT sometimes does not involve Majelis Ta'lim of Mosque level, so the contribution posed BKMT Jayapura is not yet felt. The research aims to determine the role of managers in developing the organization, the form of activities undertaken, and the inhibitory factor of activities conducted by BKMT Jayapura. The management of BKMT Jayapura is expected to be able to conduct communication with the founder of BKMT Jayapura so that the exchange process, understanding the information conducted between the Board with the founder of BKMT. The importance of norms communication, the value in the actions of its members conducting activities, there is no appreciation for managers who have a large contribution to the organization, planning the personnel, identifying the work, placing new members taken from the district level BKMT, implementing socialization on the new officers on the task, responsibility to be carried out. Training and development conducted for BKMT managers constraints of available funds, the contact between the board of BKMT Jayapura to know each other so as to facilitate managers interconnected, decision making is done individually, but some are done in a group. Decision making by the leadership of BKMT based on certain considerations, or based on the properties of its urgency, coordination is done if there is work done together, carrying out personal exchange between the managers in the body BKMT and with the caretaker in the province or BKMT at the district level.